USING INTERACTIVE METHODS IN UZBEK LANGUAGE HISTORY LESSONS - Tojiyeva Muxlisa Samidin qizi (International Journal of Literature and Language Studies, 2026)
This paper explores the application of interactive teaching methods in Uzbek language history lessons. The history of the Uzbek language is a rich and complex subject, covering centuries of linguistic evolution, cultural influences, and political changes. However, traditional lecturebased approaches often fail to engage students or help them grasp the dynamic nature of language development. Interactive methods – such as roleplaying historical linguistic scenarios, projectbased learning, group discussions, digital timeline creation, and comparative text analysis – offer a more effective way to bring the subject to life. Drawing on classroom observations and pedagogical research, the study demonstrates that interactive techniques significantly increase student motivation, deepen understanding, and develop critical thinking skills. The paper provides practical examples of how these methods can be integrated into the Uzbek language history curriculum and discusses the challenges of implementation, including large class sizes and limited resources. Recommendations are offered for educators, curriculum designers, and teacher trainers.